PEMANFAATAN SERAT JARINGAN VASKULAR BATANG KELAPA SAWIT SEBAGAI BAHAN BAKU KERTAS (Useful of Fibers from Oil Palm Trunk as Raw Material of Paper) - Nasution, Zainal Abidin (Baristand Industri Banda Aceh, 2014)
Oil palm trunk will have been farming waste contain fibre (vascularbundles) and powder (parenchym), to be able advantage of sources of fibers and starch.Fibers of vascular bundles from oil palm trunk can be obtained by degradation oil palmtrunk against time with long duration. Or can be obtained from separation vascularbundles and parenchym by mechanization. The process of making wood pulp palm oil(palm stem vascular bundles) conducted by the soda. Cooking-I, by cooker with 1,5%NaOH solution for 2 hours. Cooking-I is to reduce lignin content on the network vascular,so that consumption and subsequent concentration of the solution cookers to reduced, inorder to ovoid damage to ripening fibers. Yield of cooking-I is 78%. Cooking-II, by cookerpressure vessels with a solution of 3% NaOH at temperatur 146oC (4,2 atm) for 4 hours.And next, expected penetration into the fiber network solution cooking to vascular fibers.Yield of cooking-II is 73%. Pulp from the cooking was washing free black liquor, bleachedand refined or blended. Characteristrics of paper from fibers vascular bundles are : Width = 0,2821 mm up to 0,4033 mm, Grammature = 78,3 gr/m2 up to 105,9 gr/m2, Tensilestrenght = 1,14 kN up to 1,40 kN, Tear strenght = 329,1 mN up to 378,9 mN, Index tensilestrenght = 0,0017 kN-m/gr up to 0,0257 kN-m/gr, Index tear strenght = 3,1418 mN-m2/grup to 4,8080 mN-m2/gr.